ANALYSING INTEGER DIVISION KNOWLEDGE AND SKILLS IN PROSPECTIVE PRIMARY TEACHERS - Fu'adiah, Dzikra; Nurhayati, Pipih; Emilzoli, Mario (KALAMATIKA Jurnal Pendidikan Matematika, 2024)
This study aims to investigate prospective primary (MI) teachers’ knowledge of the sign of the division result of integers, their skills in illustrating the division model of integers, and their ability to perform integer division operations. This study comprehensively describes prospective MI teachers' work on integer division problems through a descriptive qualitative research approach. Data were collected using a test. The participants were considered to have received instruction on integer division material, thus preparing them to become teachers who understand the concept of integer division. They demonstrated the correct knowledge regarding the sign of the division result of integers. They illustrated the division models of integers in four categories: (1) unable to illustrate the division models of integers, (2) illustrating integer division models incorrectly, (3) illustrating integer division models correctly but without demonstrating their understanding, and (4) illustrating integer division models correctly and understandably. The skills of the MI teachers in performing integer division included using downward division by separating integer signs correctly, using downward division by attaching integer signs correctly, using downward division by attaching integer signs incorrectly, and not explaining any methods for operating with integers. This study's results can serve as a basis for improving the learning process, curriculum, and training programs for prospective MI teachers.